STUDY OF THE ADSORPTION-DESORPTION PROCESS OF THE METALS: Cu, Mn, Pb and Zn IN VOLCANIC SOILS. - Sylvia Violeta Copaja; Danitza Ferrer (Journal of the Chilean Chemical Society, 2025)
ABSTRACTThe study of the processes of adsorption – desorption of metallic trace elements or heavy metals in soils is crucial for the proposal of effective strategies for mitigation, reduction or elimination of these in natural systems.This work presents a study of the processes of adsorption and/desorption of Cu, Mn, Pb and Zn in two Chilean soils: Alhué (VI Region, Chile) and Nueva Braunau (X Region, Chile), both of volcanic origin and agricultural use.The soil samples studied were dried and sieved (< 2 mm or < 0.63 mm). The physicochemical characterization: pH, CE, MO, COT, N, P, CIC and texture was performed using described methods. The total fraction of each metal was obtained by microwave digestion with HNO3 and HCl. The contact time needed to reach equilibrium was determined by leaving the soil with the metal solution at different times (3, 6, 12, 24, 48 and 72 hours). The adsorption process was performed by a batch experiment, mixing different aliquots of metal solution with balancing solution (KNO3) 0.1 molL-1. Desorption was made from the 50/50 metal/balancing solution. The metals in the different soil samples and the total fraction in the soil were determined by AAS.The distribution of the total fraction of metals in decreasing order is in Alhué soil: Mn > Pb > Cu > Zn and in Nueva Braunau soil: Mn > Pb > Zn > Cu. It was determined that the contact time at which metals reach equilibrium is 48 hours for both soils, fitting appropriately with Elovich's model.The decreasing order of adsorption in the Alhué soil is: Cu > Zn > Pb > Mn and in the Nueva Braunau soil: Cu > Pb > Zn > Mn.The determination of the type of adsorption was made through the application of adsorption models of Langmuir and Freundlich. Cu adjusted according to the Langmuir model on both soils. Cu and Zn conformed to Freunlich's model.The desorption results are: Alhué soil: Pb > Mn > Zn > Cu and Nueva Braunau soil: Mn > Pb > Zn > Cu.The negative ΔG° (Gibbs free energy change) values obtained in the presents study indicate that the adsorption of metals onto soil samples is a spontaneous process and that the adsorption was an exothermic process excep for Mn in both soils.